Prevalence and Mortality Rates of Acute Kidney Injury among Critically Ill Patients: A Retrospective Study - Randa I. Farah; Othman A. Alfuqaha; Ali R. Younes; Hasan A. Mahmoud; Alhareth M. Al-Jboor; Mohammad M. Karajeh; Mohammad Z. Al-Masadeh; Omar I. Murad; Nathir Obeidat (Critical Care Research and Practice)
Acute kidney injury (AKI) poses a significant challenge in critically ill patients. To determine the prevalence, risk factors, and mortality rate of AKI among nonsurgical critically ill patients in Jordan University Hospital, we conducted a retrospective study using a consecutive sampling method, including 457 nonsurgical critically ill patients admitted to the medical intensive care unit (MICU) from January to June 2021. The mean age was 63.8 ± 18 years, with 196 (42.8%) developing AKI during their stay in the MICU. Among AKI nonsurgical patients, pulmonary diseases (n = 52; 34.5%) emerged as the primary cause for admission, exhibiting the highest prevalence, followed by sepsis (n = 40; 20.4%). Furthermore, we found that older age (adjusted OR (AOR): 1.04; 95% confidence interval (CI): 1.04–1.06; p=0.003), preadmission use of diuretics (AOR: 2.12; 95% CI: 1.06–4.25; p=0.03), use of ventilators (2.19; 95% CI: 1.12–2.29; p=0.02), and vasopressor use during MICU stay (AOR: 4.25; 95% CI: 2.1308.47; p=0.001) were observed to have higher mortality rates. Prior utilization of statins before admission exhibited a significant association with reduced mortality rate (AOR: 0.42; 95% CI: 0.2–0.85; p=0.02). Finally, AKI was associated with a higher mortality rate during MICU stay (AOR: 2.44; 95% CI: 1.07–5.56; p=0.03). The prevalence of AKI among nonsurgical patients during MICU stay is higher than what has been reported previously in the literature, which highlights the nuanced importance of identifying more factors contributing to AKI in developing countries, and hence providing preventive measures and adhering to global strategies are recommended.